Strategies to Enhance Drug Permeability across Biological Barriers-A Summary of This Important Special Issue - Jingyuan Wen; Yuan Huang (MDPI AG, 2023)
This Special Issue, "Strategies to Enhance Drug Permeability across Biological Barriers", is hosted by Pharmaceutics and highlights the recent technological advancements for overcoming biological barriers and improving drug permeability and absorption [...]